(untitled) (Open Herald: Periodical of Methodical Research, 2024)
In today’s world, trade marketing increasingly relies on the use of data and analytics to optimize retail strategies. With the advancement of technology and the availability of large amounts of data, companies are gaining more accurate analysis of consumer behavior and making informed decisions. In this article we explore modern technologies and analytical methods that allow you to optimize retail strategies in trade marketing. We focus on examples of the use of data and analytics in various aspects of trade marketing, as well as on identifying effective benefits and problems in their implementation.